Essential Hypertension in Ten & Half Years Old Boy: A Case Report - Roy, Ranjit Ranjan; Qader, Md Abdul; Matin, Abdul; Islam, Md Rafiqul; Begum, Afroza (Journal of Shaheed Suhrawardy Medical College, 2013)
Childhood hypertension (HTN) is important cause of morbidity and mortality. Most of the cases of childhood HTN are secondary to an underlying disorder. In this case report a ten & half yr old boy presented with neck pain associated with headache. Both of his parents are hypertensive. Most of the time he spent at home playing games in computer and watching television. On examination, blood pressure (BP) was 140/95 mm of Hg which was above 99th percentile for his age and height. Examination of eyes and other systems revealed normal. Ultrasonography of abdomen was normal, colour Doppler ultrasonography of renal vessels showed normal, and CT scan of abdomen was also normal including normal adrenal gland and sympathetic chain. Then the child was treated with tab. losartan potassium, then gradually BP become bellow 90th percentile. Ultimately the child was discharged when his blood pressure was 100/70 mm of Hg, which was on 50th percentile with counselling and advised for follow up. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16253 J Shaheed Suhrawardy Med Coll, 2013;5(1):69-71